3224 Impact of aortic arch anatomy on technical performance and clinical outcomes in acute ischemic stroke patients. (27th March 2019) - Knox, Joseph A; Ch'ang, Judy; Murph, Daniel; Mccoy, David; Cooke, Daniel
Abstract : OBJECTIVES/SPECIFIC AIMS: This study aims to examine the relative impact of aortic arch and carotid artery anatomy on the procedural times and clinical outcomes in patients who have suffered acute ischemic strokes (AIS). Mechanical thrombectomy remains the gold-standard of care for large vessel ischemic stroke. Given that short procedural times are necessary for good clinical outcomes, arterial access is an important technical consideration. It has been recently demonstrated that abnormal carotid artery anatomy can increase endovascular procedure times in this patient population. However, there are no studies examining the impact of aortic arch anatomy on operative times. Additionally, no studies have looked at the impact of aortic arch and carotid artery tortuosity on clinical outcomes in AIS. Thus, we sought to exam the influence of various aortic arch and carotid artery anatomic variables on interventional procedure times and clinical outcomes. METHODS/STUDY POPULATION: We included 56 patients who underwent embolectomy with successful revascularization for acute ischemic stroke in the anterior circulation from a period of 01/2016-05/2018. The average age was 71 (+/− 17 years) with 39% being male. We calculated anatomic variables on the affected side from CT angiograms immediately prior to embolectomy including the medial-to-lateral span, as well as the anterior-to-posterior span, of both the aortic arch and carotid arteries. In addition, the take-off angle of the respective vessel (left common carotid or right brachiocephalic) was calculated. Charts were reviewed for procedural times and epidemiologic information (HTN, HLD, DM, CAD and Afib). Modified Rankin Scale (mRS) was calculated from PT/OT and outpatient neurology notes. Partial correlation coefficients were performed between anatomic variables, temporal variables and outcome variables after adjustment for age, gender and epidemiologic information. RESULTS/ANTICIPATED RESULTS: There was a significant positive correlation between procedure time (time at groin puncture to time at reperfusion) and take-off angle. There were no other significant correlations between anatomic measures and procedure time. In addition, there was as a significant positive correlation between both procedure time and time from last seen normal to reperfusion and delta mRS (the difference between pre-stroke and post-stroke mRS). DISCUSSION/SIGNIFICANCE OF IMPACT: These results suggest that patients with larger take-off angles have an association with longer procedural times and worse outcomes. If these patients can be effectively identified prior to the procedure, operators could feasibly use a non-femoral access method initially to reduce procedure time.